Digital Marketing Strategy in Increasing The Competitiveness of Micro Businesses in Rafika Dompo Pisang Products - Citra Olii; Melizubaida Mahmud; Kasim, Mamang; Hafid, Radia; Gani, Imam Prawiranegara (International Forum of Researchers and Lecturers, 2025)
This study aims to describe relevant digital marketing strategies to improve the competitiveness of the Rafika Dompo Banana MSME in Soguo Village, Bolaang Uki District, South Bolaang Mongondow Regency, and analyze the supporting and inhibiting factors in implementing these strategies. This study uses a qualitative approach with a case study method. Data collection was conducted through observation, in-depth interviews with the owner, employees, and consumers, and documentation. The data analysis technique used a narrative inquiry model. The results of the study indicate that the digital marketing implementation of the Rafika Dompo Pisang MSME is still at a basic stage, utilizing WhatsApp and Facebook organically with simple content managed directly by the owner. Limited digital knowledge, minimal paid promotion budget, and suboptimal utilization of marketplace platforms are the main obstacles. Nevertheless, promotion through social media has been proven to increase product visibility and reach consumers. Supporting factors include maintained product quality, government support for licensing, and consignment collaboration. Consumer perception of the product is very positive, and existing digital promotions are considered to assist in purchasing decisions. In conclusion, the implemented digital marketing strategy is still simple but has a positive impact. Increasing competitiveness requires strategy optimization through increased digital literacy, platform diversification, and more planned resource allocation.